Підсумки інтродукції паркових троянд у Національному ботсаду ім. М.М. Гришка НАН України - Rubtsova, O.L.; Klimenko, A.V.; Chizhan'kova, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of introduction and principles of exposition's creation of shrubs roses in M.M. Gryshko National Botanical Gardens are emphasized.